The Analysis of Students’ Cognitive Learning Outcomes through the Implementation of Blended Learning in Junior High Schools Science - Sapta Aji, Rianda Herlan; Astuti, Budi; Saptono, Sigit (Universitas Negeri Semarang)
Learning in the 21st century needs to accommodate e-learning without having to leave face to face in order to keep it interesting and effective. The innovation that can be done is through the implementation of blended learning to combine the two. Especially during the Covid-19 pandemic, students learn from home so online learning is a must. The purpose of this study is to analyze students' cognitive learning outcomes through the implementation of blended learning in Science in the material on temperature and its changes in Junior High School. This experimental research used a pretest-posttest control group design which contained an experimental class (blended learning) and a control class (online learning only). The sample of this research is the 7th grade students at SMPIT Harapan Bunda Semarang. Collecting data in this study used test methods in the form of pretest and posttest. For data analysis used analysis of learning outcomes completeness, N-gain test and t-test. Based on data analysis, it was found that the implementation of blended learning in Junior high school in science learning was effective enough to improve students’ cognitive learning outcomes compared to face-to-face online learning only. This is indicated by the percentage of student learning completeness in the experimental class of 79.66%, while in the control class it is 68.33%. From the results of the N-gain test and t-test it was also found that the experimental class had a higher increase of 0.50, while the control class was 0.44. Key words: blended learning, cognitive learning outcomes, learning mastery